Durable Clinical and Immunologic Advantage of Living Donor Liver Transplantation in Children. Issue 6 (June 2018) - Przybyszewski, Eric M.; Verna, Elizabeth C.; Lobritto, Steven J.; Martinez, Mercedes; Vittorio, Jennifer M.; Fox, Alyson N.; Samstein, Benjamin; Kato, Tomoaki; Griesemer, Adam D.; Emond, Jean C.
Abstract : Background: Despite high survival in pediatric living donor liver transplantation (LDLT), only 10% of liver transplants in children in the United States are from living donors, reflecting reluctance to embrace this approach. In addition to optimal timing and graft quality, LDLT may offer immunologic benefit because most donors are haploidentical parents. We sought to quantify the benefit of LDLT compared to deceased donor liver transplantation (DDLT) using granular clinical and immunologic outcomes over the long term. Methods: A retrospective cohort of children (age <18 years) surviving 1 year or longer posttransplant was evaluated to determine the impact of donor type on graft survival and immunologic outcomes. Results: Two hundred forty-one children (177 DDLT and 64 LDLT) were assessed. In multivariable analysis, LDLT was associated with a lower rate of acute cellular rejection (hazard ratio [HR], 0.53; 95% confidence interval [CI], 0.29-0.98; P = 0.04), a lower rate of chronic rejection (HR, 0.12; 95% CI, 0.03-0.56; P = 0.007), better graft survival on monotherapy immunosuppression at 3 years posttransplant (87.7% vs 46.7%; odds ratio, 7.41; 95% CI, 2.80-19.66; P < 0.001), and a lower rate of graft loss (HR, 0.29; 95% CI, 0.10-0.88; P = 0.03). Graft type was not an independent predictor of posttransplant mortality (LDLT HR, 0.57; 95% CI, 0.16-2.01; P = 0.38). Maternal graft LDLT was associated with a lower rate of acute cellular rejection (HR, 0.13; 95% CI, 0.03-0.64; P = 0.01) and posttransplant lymphoproliferative disorder (HR, 0.04; 95% CI, 0.004-0.44; P = 0.008) compared with paternal grafts. Conclusions: This study demonstrates the potential benefit of LDLT, particularly with maternal grafts, for pediatric liver transplant recipients on multiple clinical parameters over long-term follow-up. Abstract : By comparing the outcome following live (LDLT) vs deceased donor liver transplantation in 241 children (age < 118) surviving ≥ 1-year posttransplant, the authors demonstrate the potential benefit of LDLT, particularly with maternal grafts, for pediatric recipients, on multiple immunological-related parameters.